Dynamic Alignment Analysis in the Osteoarthritic Knee Using Computer Navigation - Larrainzar-Garijo, Ricardo; Murillo-Vizuete, David; Garcia-Bogalo, Raul; Escobar-Anton, David; Horna-Castiñeiras, Lissette; Peralta-Molero, Juan Vicente (The Journal of Knee Surgery, 2017)
The lower limb alignment is influenced by the geometry of the joint surfaces and surrounding soft tissue tension. The mechanical behavior changes in a normal, osteoarthritic, and postoperative knee. The purpose of this study is to determine the dynamic coronal femoral tibial mechanical angle (FTMA) in osteoarthritic knees using computer navigation. The authors hypothesize that there are different varus-valgus patterns between flexion and extension in the osteoarthritic knee. We conducted a transversal observational study and included patients with osteoarthritis who underwent primary navigation TKA (Orthopilot version 4.2; B. Braun Aesculap, Tuttlingen, Germany). In total, 98 consecutive patients with 100 osteoarthritic knee joints, on which total knee arthroplasty was performed in our institution from 2009 to 2010, were enrolled in this prospective study. The FTMA was measured with the patient supine with maximum knee extension possible (considering the value as 0), 30, 60, and 90 degrees. All FMTA data obtained were segmented by hierarchic cluster measuring method. Through the clustering system, five segments were generated for varus patients and three for valgus patients: expected varus, expected valgus, severe varus, severe valgus, structured varus, structured valgus, concave varus, mixed varus-valgus, and mixed valgus-varus. The findings of the present study have demonstrated that there is a well-defined dynamic alignment in osteoarthritic knees, resulting in a wide kinematic variation in the coronal FTMA between flexion and full extension. Further studies will be necessary to determine whether this dynamic approach to FTMA has clinical utility in the surgeon's decision-making process.
Keywords: dynamic alignment; femorotibial mechanical angle; lower limb alignment; varus-valgus pattern